Ganiyev, Khanlar - (:unkn) unknown (My University, 2026)
Khanlar Ilgar oglu Ganiyev graduated from Azerbaijan State Economic University in 2012 with a Bachelor’s degree in International Trade and obtained a Master’s degree in International Economic Relations from the same university in 2015. He subsequently earned a degree in Civil Engineering from the Azerbaijan University of Architecture and Construction. He holds a Doctor of Philosophy (PhD) in Economics and the academic rank of Senior Lecturer. Dr. Ganiyev began his professional career in 2012 at UNIBANK Commercial Bank as a Consumer Loans Specialist. In 2014, he joined Sumgait Technologies Park (STP), where he worked in the Marketing Department and later in International Economic Relations. Since 2016, Dr. Ganiyev has been working at AzUAC. He has served as Head of the Laboratory at the Department of Transport Construction and Road Traffic Organization and as an Assistant Lecturer at the Department of Economic Theory and Marketing. His current teaching activities include Global Business, Career Planning, and Soft Skills. He has participated in several international academic and professional development programmes, including Erasmus+ KA1 and KA2 projects, the KOICA Capacity Building programme, and academic training at Université Paris 1 Panthéon-Sorbonne. He is also a certified Project Management Specialist (IPMA) and serves as an expert in management systems and higher education accreditation. Dr. Ganiyev is the author of one monograph and nearly 50 scientific publications, including five articles in journals indexed in Scopus and Web of Science. His research interests include regional infrastructure development, global business, educational management and standardization, and the socio-economic impact of transportation and logistics systems.